Conhecimento e uso de textos multimodais no ensino de leitura nos Anos Finais do Ensino Fundamental - Ribeiro, Taiane da Silva Lira (2023)
The reading of multimodal texts is still little explored in the reading practices proposed by Portuguese language teachers in the final years of elementary school (Ribeiro, 2016). We often witness the sharing of anxieties and insecurities by many teaching colleagues, which reveal the absence and/or insufficiency of initial and continued training focused on working with multimodal texts. In this context, we define our object of study as the reading of multimodal texts in the Final Years of Elementary School, based on the work of Portuguese language teachers at schools under the jurisdiction of the 15th GRE, Corrente – PI. As a starting point for our reflection, we took the following questions: What is the theoretical-methodological knowledge of these teachers when working with reading multimodal texts? What are the pedagogical advances and/or innovations regarding the reading practices of multimodal texts adopted by the research subjects? Thus, the general objective of this research is to investigate the knowledge and use of multimodal texts in teaching reading in the final years of elementary school by Portuguese language teachers who work in Final Years of Elementary School classes in schools under the jurisdiction of the 15th GRE, Current – PI. And as specific objectives: i) – analyze the theoretical perception of Portuguese language teachers in the Final Years of Elementary School regarding multimodality and multimodal texts and readings; ii) identify whether the subjects of this research know the proposals and guidelines of the BNCC, the Piauí Curriculum, and/or other documents for working with the reading of multimodal texts in the final years of Elementary School; iii) investigate whether and how the reading practices adopted include the reading of multimodal texts in order to identify possible advances and/or challenges. For this research, we took as a basis Ribeiro's discussions (2016; 2021) about reading and multimodal texts based on the premise that all texts are multimodal and we also established a dialogue with some authors, such as Dionísio and Vasconcelos (2013) who present some important aspects that can guide and facilitate the reading of multimodal texts and Barros (2009) who presents fundamental strategies for reading multimodal texts among others and; with official documents the National Common Curricular Base (BNNC, Brasil, 2018) and Currículo do Piauí (Brasil, 2020). To achieve the proposed objectives, the research used a qualitative (Guerra, 2014), exploratory (Prodanov; Freitas, 2013) approach. The research field of this study covered 09 (nine) public schools of the State Education Network under the jurisdiction of the 15th GRE, Corrente – PI that offer the Final Years of Elementary Education, distributed in 07 (seven) municipalities. As research subjects, 20 (twenty) Portuguese language teachers who work in Final Years of Elementary School classes in rural schools collaborated. As technical procedures and data collection instruments, we used bibliographical research, sampling survey, carried out through the application of a semi-structured online questionnaire via Google Forms. The results indicate that the theoretical-methodological knowledge of Portuguese language teachers in the Final Years of Elementary Education in schools under the jurisdiction of the 15th GRE, Corrente – PI for working with reading multimodal texts is still very precarious and insufficient, which can compromise their practice in the classroom. Based on these results, we developed a didactic proposal with the aim of contributing to the teaching of reading multimodal texts; This proposal is materialized in a Pedagogical Notebook consisting of thematic units through which we propose theoretical-methodological reflections on the reading of multimodal texts.